Systematic of Terpidinae Kluge (Ephemeroptera: Leptophlebiidae) - Marulanda-Lopez, Jhon Faber (2020)
Leptophlebiidae is one of the most diversified groups of Ephemeroptera, both taxonomically as morphologically, and with a worldwide distribution with exception of Antarctica. Recently, Leptophlebiidae was divided into eight subfamilies, among them Terpidinae. Terpidinae is composed by the genera Terpides, Fittkaulus and Tikuna and its occurrence is restricted to the Neotropical region. Among the subfamilies of Leptophlebiidae, members of Terpidinae present particular morphological characteristics, as hypognathous mouthparts and presence of swimming setae in caudal filaments. The characters traditionally used in Terpidinae taxonomy are wing venation, shape of male genitalia in imagos, egg morphology, mouthparts morphology and type and disposition of setae, shape of the claws, abdominal color pattern, and shape of the gills in the nymphs. However, some species present the same abdominal color pattern and the morphology of the male genitalia is very conservative. In this context, additional morphological characteristics are necessary to complement the traditional characters used in the systematic of the subfamily. In addition, the subfamily was not proposed using a quantitative phylogenetic analysis and the phylogenetic relationships between Terpidinae species are unknown. The aim in this investigation is to test the current classification of Terpidinae using a morphology-based phylogenetic analysis. As a result, the monophyly of Terpidinae was recovered with good support. Castanophlebiinae was found to be the sister group of Terpidinae and Tikuna was recovered as sister group of Fittkaulus. The diagnosis of all genera and species of Terpidinae are presented and an interactive illustrated key for the identification of Terpidinae has also been proposed. Additionally, the evolution of some selected morphological characteristics used a priori in the classification of the group are discussed. Keywords: Castanophlebiinae. Fittkaulus. Terpides lineage. Neotropic. Tikuna.